Efektivitas Penggunaan Media Pembelajaran Interaktif Berbasis Game Puzzle dalam Meningkatkan Minat Belajar Siswa pada Mata Pelajaran Pendidikan Agama Islam di SMPN 3 Padang Panjang - Paulana, Rezi; Kanus, Oktari (Lembaga Yasin AlSys, 2025)
This study is motivated by the need for teachers to develop innovative learning strategies that enhance student interest through engaging and interactive media. One promising approach is the use of puzzle games as a learning medium to facilitate understanding and encourage active student participation. The objective of this research is to examine the effectiveness of interactive learning media based on puzzle games in improving students’ interest and academic achievement in Islamic Religious Education at SMPN 3 Padang Panjang. A quantitative method with a pre-experimental one-group pretest-posttest design was employed, involving 28 students as the sample. Data were collected through a pretest, treatment using the puzzle game media, posttest, and a learning interest questionnaire, and analyzed using descriptive and inferential statistics with the aid of SPSS. The results indicate a significant increase in the average learning outcome from 39.18 to 79.18 after the intervention, with a statistically significant Wilcoxon Signed Rank test result (p = 0.001). Linear regression analysis showed a positive effect of the media on learning outcomes (p = 0.014), and an N-Gain score of 0.6532 indicated a moderate to high improvement consistently across students. The study concludes that puzzle game media are effective in enhancing students’ interest and academic performance, while also promoting active participation in the learning process. The implications of this study span pedagogical and psychological aspects, suggesting that interactive media serve as an innovative strategy to enrich teaching methods, boost motivation, and integratively foster students' spiritual and moral character.